Enhancing Van der Waals Interactions of Functionalized UiO‐66 with Non‐polar Adsorbates: The Unique Effect of para Hydroxyl Groups. Issue 8 (4th January 2018) - Tovar, Trenton M.; Iordanov, Ivan; Sava Gallis, Dorina F.; DeCoste, Jared B.
Abstract: UiO‐66 is a highly stable metal‐organic framework (MOF) that has garnered interest for many adsorption applications. For small, nonpolar adsorbates, physisorption is dominated by weak Van der Waals interactions limiting the adsorption capacity. A common strategy to enhance the adsorption properties of isoreticular MOFs, such as UiO‐66, is to add functional groups to the organic linker. Low and high pressure O2 isotherms were measured on UiO‐66 MOFs functionalized with electron donating and withdrawing groups. It was found that the electron donating effects of ‐NH2, ‐OH, and ‐OCF3 groups enhance the uptake of O2 . Interestingly, a significant enhancement in both the binding energy and adsorption capacity of O2 was observed for UiO‐66‐(OH)2 ‐p, which has two ‐OH groups para from one another. Density functional theory (DFT) simulations were used to calculate the binding energy of oxygen to each MOF, which trended with the adsorption capacity and agreed well with the heats of adsorption calculated from the Toth model fit to multi‐temperature isotherms. DFT simulations also determined the highest energy binding site to be on top of the electron π‐cloud of the aromatic ring of the ligand, with a direct trend of the binding energy with low pressure adsorption capacity. Uniquely, DFT found that oxygen molecules adsorbed to UiO‐66‐(OH)2 ‐p prefer to align parallel to the ‐OH groups on the aromatic ring. Similar effects for the electron donation of the functional groups were observed for the low pressure adsorption of N2, CH4, and CO2 . Abstract : Extraordinary adsorption : Para hydroxy groups in the metal‐organic framework UiO‐66 enhance the uptake of the non‐polar adsorbates O2, N2, CH4, and CO2 through a unique binding site in the π‐cloud parallel to the functional groups.